2023
DOI: 10.1186/s12870-023-04230-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen metabolism affects kentucky bluegrass rhizome expansion

Abstract: Background Rhizome is vital for carbon and nitrogen metabolism of the whole plant. However, the effect of carbon and nitrogen in the rhizome on rhizome expansion remains unclear. Results Three wild Kentucky bluegrass (Poa pratensis L.) germplasms with different rhizome expansion capacity (strong expansion capacity, ‘YZ’; medium expansion capacity, ‘WY’; and weak expansion capacity, ‘AD’) were planted in the field and the rhizomes number, tiller num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…In other plant species, such as creeping bentgrass (Agrostis stolonifera L.), an elevated carbon dioxide (CO 2 ) concentration promotes stolon growth and increases the accumulation of glucose, sucrose, fructose, and endogenous IAA at the stolon nodes and internodes, resulting in longer stolons and larger stolon shoot biomass [11]. Kentucky bluegrass (Poa pratensis L.) with more ramets also exhibits a significant increase in the soluble sugar content in the rhizome [12]. In addition, studies on strawberries have revealed that auxin and CTK play antagonistic roles in controlling the development of axillary buds.…”
Section: Introductionmentioning
confidence: 99%
“…In other plant species, such as creeping bentgrass (Agrostis stolonifera L.), an elevated carbon dioxide (CO 2 ) concentration promotes stolon growth and increases the accumulation of glucose, sucrose, fructose, and endogenous IAA at the stolon nodes and internodes, resulting in longer stolons and larger stolon shoot biomass [11]. Kentucky bluegrass (Poa pratensis L.) with more ramets also exhibits a significant increase in the soluble sugar content in the rhizome [12]. In addition, studies on strawberries have revealed that auxin and CTK play antagonistic roles in controlling the development of axillary buds.…”
Section: Introductionmentioning
confidence: 99%